Perancangan Perbaikan Tata Letak Produksi untuk Meningkatkan Efisiensi Proses Produksi Decking & Pintu: Studi Kasus: CV. Cipta Karya - Mayddy Amanda, Jessica; Murnawan, Hery (Fakultas Teknik UMRI, 2025)
CV. Cipta Karya is a company engaged in the manufacturing industry sector of woodworking, furniture, sawmil, kilndry, warehouse rental, wood storage and log yard. CV. Cipta Karya implements the Make to Order system. One of the crucial challenges that arise in the production process of solid wood decking and doors is inefficiency in the arrangement of production facilities, high material handling costs, and material accumulation in the production area. This research aims to redesign the layout of production facilities by prioritizing improving the efficiency of the manufacturing process. The design is carried out through an approach of optimizing the distance between workstations and analyzing the material handling system, in order to smooth the production flow, reduce moving time, and minimize resource wastage.The research approach used includes evaluating the current layout of production facilities through the use of From-To Chart (FTC) to study and map the intensity and direction of material movement between workstations, so that inefficient flow patterns that have the potential to hinder the smooth production process can be identified, then the calculation of material handling costs (OMH), as well as analysis of the activity relationship between production facilities. Furthermore, a more optimal proposed layout was designed, which was then tested using the flexim 2025 simulation to evaluate the impact of production system efficiency.The findings of this study indicate that the proposed new layout design is able to significantly reduce the total distance of material transfer between workstations. These changes also have an impact on reducing material handling costs and increasing efficiency in the overall production process. In addition, the implementation of a more organized layout also makes a real contribution to cutting production cycle time and has positive implications for improving the overall productivity of the company.